Баллада о маленьком буксире: [стихотворение] / Иосиф Бродский - Бродский Иосиф Александрович (Азбука, 2012)
Экземпляры: ф. 2 (20120409) / Инвентарный номер: 98470 / Цена: 183.38 / Авт.знак: Б 88 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6